2018
DOI: 10.1002/jbm.b.34162
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of polyetheretherketone versus silicon nitride intervertebral spinal spacers in a caprine model

Abstract: Polyetheretherketone (PEEK) is commonly used as a spinal spacer for intervertebral fusion surgery. Unfortunately, PEEK is bioinert and does not effectively osseointegrate into living bone. In contrast, comparable spacers made of silicon nitride (Si N ) possess a surface nanostructure and chemistry that encourage appositional bone healing. This observational study was designed to compare the outcomes of these two biomaterials when implanted as spacers in an adult caprine model. Lumbar interbody fusion surgeries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Osteogenic effects of SiN were confirmed in several in vitro tests with different cell types, such as human osteosarcoma SaOS-2 cells ( Pezzotti et al, 2016 ; Pezzotti et al, 2017b ; Zanocco et al, 2019 ), mouse bone marrow stromal cells (BMSCs) ( Pezzotti et al, 2017a ), and human BMSCs ( Amaral et al, 2002 ). The effectiveness of SiN was further confirmed in several in vivo studies using a goat lumbar interbody fusion model ( Kersten et al, 2019 ), a rat calvarial defect model ( Webster et al, 2012 ), and a murine tibial implant model ( Ishikawa et al, 2017 ). However, the brittleness and lack of resilience, common disadvantages of ceramic biomaterials, make it problematic to use SiN alone as a scaffold.…”
Section: Introductionmentioning
confidence: 74%
“…Osteogenic effects of SiN were confirmed in several in vitro tests with different cell types, such as human osteosarcoma SaOS-2 cells ( Pezzotti et al, 2016 ; Pezzotti et al, 2017b ; Zanocco et al, 2019 ), mouse bone marrow stromal cells (BMSCs) ( Pezzotti et al, 2017a ), and human BMSCs ( Amaral et al, 2002 ). The effectiveness of SiN was further confirmed in several in vivo studies using a goat lumbar interbody fusion model ( Kersten et al, 2019 ), a rat calvarial defect model ( Webster et al, 2012 ), and a murine tibial implant model ( Ishikawa et al, 2017 ). However, the brittleness and lack of resilience, common disadvantages of ceramic biomaterials, make it problematic to use SiN alone as a scaffold.…”
Section: Introductionmentioning
confidence: 74%
“…In interbody fusion, another critical determinant is the new bone formation around the intervertebral fusion cage. , A bioactive material should have the capacity to stimulate biological response to realize effective osteogenesis. , The regenerative ability of the material could be improved by optimizing composition or incorporating bioactive ions that play a pivotal role in osteogenic process. In our previous study, we demonstrated that the presence of CS incorporated into PEEK could effectively release the bioactive Ca 2+ and Si 4+ ions which exerted a positive influence on the osteogenic differentiation of preosteoblasts in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…New medical devices should be compared to the gold standard for their clinical performance. Kersten et al [ 73 ] compared the bone formation ability of Si 3 N 4 and PEEK in lumbar interbody fusion surgeries using a caprine model. The results demonstrated that Si 3 N 4 spacers were not inferior to PEEK in bone-implant contact (BIC) and biodynamic stability, and they were superior in promoting arthrodesis.…”
Section: Medical Application Of Si 3 Nmentioning
confidence: 99%